The creatine kinase energy transport system in the failing mouse heart. - Lygate, C; Fischer, A; Sebag-Montefiore, L; Wallis, J; ten Hove, M; Neubauer, S (2007)
Characteristic alterations of the creatine kinase (CK) system occur in heart failure and may contribute to contractile dysfunction. We examined two mouse models of chronic cardiac stress, transverse aortic constriction (TAC) and coronary artery ligation (CAL), and examined the relationship of CK system changes with hypertrophy and heart failure development. C57Bl/6 mice were subjected to TAC or sham surgery and sacrificed after 2-10 weeks according to echocardiographic criteria of myocardial hypertrophy and function to create four groups representing progressive dysfunction from normal, through compensated hypertrophy, to heart failure. Only mice with congestive heart failure had LV total creatine concentration and total CK activity significantly lower than sham values (11% and 30% lower, respectively). However for all aortic banded mice, a linear relationship was observed between ejection fraction and estimated maximal CK reaction velocity. Mice with heart failure also had corresponding decreases in the activities of the Mito-, MM-, and MB-CK isoenzymes, while the BB isoform remained unchanged. To determine whether these changes were model specific, mice were subjected to CAL or sham operation and followed for 7 weeks. Quantitative changes in total creatine, total CK activity, Mito-CK and MM-CK activities were similar for CAL and TAC mice. We conclude that alterations in the creatine kinase system occur during heart failure in mice qualitatively similar to those occurring in larger animals and humans, suggesting that mice are a suitable model for studying the role of such changes in the pathogenesis of heart failure.